Concept and controversy : sixty years of taking ideas to market - Rostow, W. W. (Walt Whitman), 1916-2003 (University of Texas Press, 2003)
"A trusted advisor to Presidents Eisenhower, Kennedy, and Johnson and one of America's leading professors of economic history, W.W. Rostow has helped shape the intellectual debate and governmental policies on major economic, political, and military issues since World War II. In this thought-provoking memoir, he takes a retrospective look at eleven key policy problems with which he has been involved to show how ideas flow into concrete action and how actions taken or not taken in the short term actually determine the long run that we call "the future.""--Jacket.